Hubungan halaju denyut ultrasonik-kekuatan mampatan konkrit: Kesan nisbah batu baur-simen, nisbah air simen dalam kaedah pengawetan berbeza - Kamarudin Mohd Yusof, (1990)

(untitled)
The effects of aggregate-cement and water-cement ratios on the relationship between ultrasonic pulse velocities and the cube compressive strength of concrete under continues wet curing and wet curing for specilic periods were studied. The relationship of the velocity with the compressive strength almost unaffected by the aggregate-cement ratios between 4.8 and 6.8, but the variation of water-cement ratio between 0.45 and 0.67 has some effect. The differences become more pronounced in the wet cured samples which have been exposed to the laboratory conditions. The ultrasonic velocities of similar samples and cured in similar manner but were tested at different ages follow the same velocity-strength relationship